Comparative genomics reveals a unique nitrogen-carbon balance system in Asteraceae - Fei Shen; Y Z Qin; R. Wang; Xin Huang; Ying Wang; Tian‐Gang Gao; Junna He; Yue Zhou; Yuannian Jiao; Jianhua Wei; Lei Li; Xiaozeng Yang (2023)
Abstract The Asteraceae (daisy family) is one of the largest families of plants. The genetic basis for its high biodiversity and excellent adaptability has not been elucidated. Here, we compare the genomes of 29 terrestrial plant species, including two de novo chromosome-scale genome assemblies for stem lettuce, a member of Asteraceae, and Scaevola taccada , a member of Goodeniaceae that is one of the closest outgroups of Asteraceae. We show that Asteraceae originated ~80 million years ago and experienced repeated paleopolyploidization. PII, the universal regulator of nitrogen-carbon (N-C) assimilation present in almost all domains of life, has conspicuously lost across Asteraceae. Meanwhile, Asteraceae has stepwise upgraded the N-C balance system via paleopolyploidization and tandem duplications of key metabolic genes, resulting in enhanced nitrogen uptake and fatty acid biosynthesis. In addition to suggesting a molecular basis for their ecological success, the unique N-C balance system reported for Asteraceae offers a potential crop improvement strategy.